2-[Carbamothioyl(2-hydroxyethyl)amino]ethyl benzoate: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The title di-substituted thiourea, C12H16N2O3S, has the hydroxylethyl and ethyl benzoate substituents bound to the same amine-N atom, and is twisted, having a (+)syn-clinal conformation with the Namine—C—C—O(hydroxyl, carbonyl) torsion angles of 49.39 (13) and 59.09 (12)°, respectively; the dihedral angle between the almost planar CN2S core and the pendent benzene ring is 69.26 (4)°. In the crystal, supramolecular layers propagating in the ac plane are formed via a combination of hydroxyl-O—H...S(thione), amine-N—H...O(hydroxyl, carbonyl) hydrogen-bonds. The layers stack along the b axis with inter-digitation of the benzene rings allowing the formation of π–π stacking [inter-centroid separation = 3.8722 (7) Å] and parallel C=O...π interactions. A computational chemistry study shows the conventional hydrogen bonding in the crystal leads to significant electrostatic stabilization but dispersion terms are also apparent, notably through the interactions involving the benzene residue.